Fatty Acid Composition, Antinutritional Factors, and Oligosaccharides Concentration of Hawaijar (An Ethnic Fermented Soyfood of India) As Affected by Genotype and Bacillus Subtilis Strain - L. Sophia Devi; Vineet Kumar; Anita Rani; Trupti Tayalkar; Priyanka Mittal; Aseem Kumar Anshu; Thangjam Anand Singh (Indonesian Association of Food Technologists, 2020)
Hawaijar is an ethnic fermented soy product from the North-East region of India. The information on the effect of soybean genotype and the Bacillus subtilis strain used for inoculation for preparing the product on the fatty acid composition, the level of antinutritional factors, such as Kunitz trypsin inhibitor (KTI) and Bowman-Birk inhibitor (BBI), and oligosaccharides is not available. In the present study, Hawaijar was prepared from two soybean genotypes using two different strains of Bacillus subtilis and investigated for the concentration of the above-mentioned biomolecules. The results showed the significant effect of genotype used on oleic, linoleic, and α-linolenic acid of the product. KTI and BBI were found absent in Hawaijar prepared from these two genotypes and two strains. Flatulence-inducing factors like raffinose and stachyose were found in very low concentration irrespective of genotype and strain. Retention of sweetness-imparting sucrose and maltose concentration in Hawaijar was genotype-dependent.